Penyesalan, Harapan dan Keputusasaan dalam I‘tirāf Karya Abū Nuwās: Kajian Psikologi Sastra - Laila Maftuhah; Arwan, Muhammad Sayyidul (Al-Ma‘rifah, 2020)
This research is aimed to express one’s phsycological condition after doing a lot of sins. He realized his mistake. He recognized all of his action. Finally he begged forgiveness to God. He had a lot of hope of mercy. He also hoped God will accept his repetance. However he was haunted of fearness if God refused his request. It will come up the hopeless because he fell there was not forgiveness for him except God. The material object of this research is the poetry of Al-I’tiraf created by Abu Nuwas and it’s translation in Indonesia. The Indonesia society especially pesantren community known it as Abu Nawas Poem. As for the formal object is inner turmoil experienced by the character in this poem which is described of writer’s life experience Abu Nuwas. Analisys method that used in this research was literature phsycology method. This analisys is done to the character mental condition who experienced regret of the sins he had done. The hope of God forgiveness and the fearness to God rejection will raise the hopeless. The result which are expected from the research is to express the feeling which experienced by the character in this poem namely a regret, wish, and hopeless.